¿Se debe revisar la determinación de la CIM de colistín en Acinetobacter baumannii? - Villanueva,Xabier (Sociedad Chilena de Infectología, 2017)
Currently, there is a controversy in how to determine the minimal inhibitory concentration (MIC) of colistin against Acinetobacter baumannii. We compared three methods, concluding that the addition of Tween-80 (0.002%) to Müller-Hinton broth in the microdilution method could improve MIC determination and it could reduce false resistance.